"Com orde minha mesmo" - Tiago Castelo Branco Lourenço (2022)
The thesis presents the socio-spatial groups of urban occupations Camilo Torres, Dandara, Eliana Silva, Emanuel Guarani Kaiowá, Rosa Leão, Esperança, Vitória and Helena Greco — the last four known as Izidora Occupations. It also discusses the trajectory of the aforementioned occupations and the experiences of technical advisors developed with these groups, taking them as urban social movements that have taken place in Belo Horizonte and region since 2008. In addition to urban occupations, it is presented the socio-social groups -space groups composed of those affected by the Samarco Dam failure in 2015 — those affected in Bento Rodrigues and Paracatu de Baixo, districts of the Municipality of Mariana in the central region of Minas Gerais —, discussing the experience of technical assistance developed until the beginning of 2018. In this work, it is proposed the study of these cases and their advisory services, dividing their development into four phases of these social movements, delving into the first three. These phases go through moments marked by direct actions, but also by others, institutionalized. Based on this, it is studied how, in the process of institutionalization, these movements are organized to meet their demands and how the technical assistance works in the different phases. With the thesis, it is systematized the production of these technical advisory services, approaching direct contact with socio-spatial groups and other modalities, such as university extension and research and teaching activities. The discussion is developed through narrative chronicles of the technical advisors in contact with a daily production of the socio-spatial groups involved, narrating a story from the perspective of the advisory in dialogue with the groups monitored, covering political organizations, residents, affected and State agents. involved with disputes.